The Change : My Great American, Postindustrial, Midlife Crisis Tour - Soderlind, Lori (Book collections on Project MUSE., 2020)
In the throes of a classic midlife crisis, Lori Soderlind takes a sabbatical from her community college job as a journalism professor. She sets out to travel across America's rusting heart with her fourteen-year-old dog, Colby, and a used camping trailer. Making pit stops in places like Buffalo and Rockford, she explores a deeply conflicted country going through its own crises and transformations. Even as she struggles with her own impulses, she finds life and resilience among the seemingly forlorn, abandoned artifacts of former industrial glory.